Treating Baby Doe: The Ethics of Uncertainty - Rhoden, Nancy K. (The Hastings Center report, 1986)
The ethical tensions inherent in all Baby Doe treatment decisions are compounded by medical uncertainty. Physicians both here and abroad have adopted various strategies. Swedish doctors tend to withhold treatment from the beginning from infants for whom statistical data suggest a grim prognosis. The British are more likely to initiate treatment but withdraw it if the infant appears likely to die or suffer severe brain damage. The trend in the U.S. is to start treating any baby who is potentially viable and continue until it is virtually certain that the infant will die. The “least worst” strategy is an individualized one: starting treatment gathering data, and then reassessing the decision.